Structure‐Based Drug Design of Mineralocorticoid Receptor Antagonists to Explore Oxosteroid Receptor Selectivity. (15th December 2016) - Nordqvist, Anneli; O'Mahony, Gavin; Fridén‐Saxin, Maria; Fredenwall, Marlene; Hogner, Anders; Granberg, Kenneth L.; Aagaard, Anna; Bäckström, Stefan; Gunnarsson, Anders; Kaminski, Tim; Xue, Yafeng; Dellsén, Anita; et al.
Abstract: The mineralocorticoid receptor (MR) is a nuclear hormone receptor involved in the regulation of body fluid and electrolyte homeostasis. In this study we explore selectivity triggers for a series of nonsteroidal MR antagonists to improve selectivity over other members of the oxosteroid receptor family. A biaryl sulfonamide compound was identified in a high‐throughput screening (HTS) campaign. The compound bound to MR with p K i =6.6, but displayed poor selectivity over the glucocorticoid receptor (GR) and the progesterone receptor (PR). Following X‐ray crystallography of MR in complex with the HTS hit, a compound library was designed that explored an induced‐fit hypothesis that required movement of the Met852 side chain. An improvement in MR selectivity of 11‐ to 79‐fold over PR and 23‐ to 234‐fold over GR was obtained. Given the U‐shaped binding conformation, macrocyclizations were explored, yielding a macrocycle that bound to MR with p K i =7.3. Two protein–ligand X‐ray structures were determined, confirming the hypothesized binding mode for the designed compounds. Abstract : Looking for MR right : A biarylsulfonamide was identified as a mineralocorticoid receptor (MR) antagonist in a high‐throughput screening campaign. Structure‐based drug design was used to improve selectivity over the oxosteroid receptors by exploring an induced‐fit pocket and expanding the ligands toward an area where the receptors differ from each other. X‐ray crystallography confirmed the binding mode and inspired macrocyclization to test conformationally restrained MR antagonists.